Transverse and Longitudinal Thermomagnetic Waves in Conducting Media - Hasanov, E.R.; Khalilova, Sh.G.; Mustafayeva, R.K. (Bulletin of the Karaganda University. “Physics” Series, 2025)
The excited thermomagnetic wave in anisotropic conducting media is analyzed theoretically at different directions of the gradient of the temperature TÑ , relative to the wave vector k . It is shown that at k T ^ Ñ (transverse wave) and at || k T ÑT|| Tk (longitudinal wave) the oscillation frequency has different values. In these two cases, the excited thermomagnetic waves are increasing. The increment of the increase in each case has different values. It is shown that the values in different directions of electrical conductivity for the excitation and for the increase of thermomagnetic waves play a major role. Depending on the selected conditions, the frequency of thermomagnetic waves changes significantly. In both cases (i.e. k T ^ÑTk and || k T ÑT|| Tk ), the choice of coordinate systems does not affect the theoretical calculation at all. The frequency and increment of thermomagnetic waves do not depend on the choice of coordinate systems. However, the choice of coordinate systems significantly affects the choice of the direction of the magnetic field and the temperature gradient. The velocity of hydrodynamic motions of charge carriers turns towards the temperature gradient. The excited magnetic field upon excitation of charge carriers (electrons) depends very much on the direction of the temperature gradient. The oscillation frequency of excitation of thermomagnetic waves depends linearly on the value of the temperature gradient. The increment of growth of excited thermomagnetic waves has different values for different values of the tensor of electrical conductivity of the medium ik s . It is stated that if the wave vector of excited waves and the constant gradient of the temperature are directed at an angle, i.e. (kkÑT = kkÑT ccossa, éëékÑT ùûù = kÑÑT ssina) theoretical calculation of the oscillation frequency and the increment of growth fails due to the high degree of the dispersion equation relative to the oscillation frequency. This theory does not consider the electric field created by the redistribution of charge carriers. The theory takes into account that the constant temperature 0T , external field 0E , and the mean free path of charge carriers satisfy the relation 0 0 0 k T eE l , 0 k is a constant. At 0 0 0 k T eE l and 0 0 0 k T > eE l a very high temperature is required, i.e. melting of the medium begins.
Өткізгіш орталардағы көлденең жəне бойлық термомагниттік толқындар
Поперечные и продольные термомагнитные волны в проводящих средах
Keywords: excitation; frequency; increment; thermomagnetic; dispersion equation; temperature gradient; wave; wave vector